WORD FORMATION PROCESS OF NEW WORDS ON POPULAR SOCIAL MEDIA PLATFORMS - Hikmah Yanti, Cita; Miftahul Barokah, Febriana (Jurnal Ilmiah Bina Bahasa, 2025)
With the rapid growth of digital communication, social media has become a dynamic space for linguistic innovation, giving rise to new and often viral words. These lexical creations reflect users’ adaptation to the fast-paced and expressive nature of online interaction. This study aims to (1) identify the types of word formation processes used in viral new words circulating on major social media platforms, and (2) explore the implicit meanings embedded in these linguistic forms. Employing a qualitative content analysis approach, data were collected from two widely used platforms, Instagram and TikTok, resulting in a sample of 25 viral new words. The analysis revealed that blending was the most frequently occurring word formation process, appearing in 10 of the 25 cases. Based on Yule’s framework, the study identified seven distinct word formation types: blending (10), coinage (1), compounding (2), clipping (2), acronyms (4), derivation (1), and multiple processes (5). These findings highlight how social media not only influences the structure of language but also shapes the meanings conveyed through it. Many of these newly formed words carry implicit meanings that reflect current social trends, cultural values, and shared online experiences, demonstrating the evolving nature of language in the digital era.